Why GM matters inside the race to transform an American icon - Holstein, William J. (Walker, 2009)
Holstein goes deep inside GM on three continents to show what's really happening within one of the country's most iconic corporations. Demonstrates how GM has already radically retooled its entire operation, from manufacturing and cost structure to design.